America's First Cosmonauts: Reflections on the Human Cost of Shuttle-Mir. Issue 1 (2nd January 2017) - Brannigan, Michael
ABSTRACT: Shuttle- Mir, the joint space exploration effort between NASA and the Russian Federal Space Agency (Roscosmos), faced a wide variety of challenges throughout its five-year run between 1993 and 1998. These included institutional differences, high costs to both the American and Russian governments, and poor public reception. The focus herein is on the personal reflections and experiences of American men and women who participated directly in the program: the seven Shuttle- Mir astronauts from the United States. These men and women joined an unprecedented exchange in which they had to train for and serve aboard a foreign space station for extended periods of time. This article utilizes archival records, official oral histories, and personal memoirs to outline three specific challenges faced in common by all of the U.S. astronauts. Primarily, they had to master both the everyday and technical intricacies of the Russian language, live in Russia during the post-Soviet economic collapse, and adapt to new institutional procedures and training methods under Roscosmos. Combined, these experiences presented serious difficulties in working with their Russian counterparts aboard the space station Mir, and made crisis situations even more hazardous. Overall, these experiences introduced yet another cost to the Shuttle- Mir program—a human one.